1989
DOI: 10.1029/jd094id13p16255
|View full text |Cite
|
Sign up to set email alerts
|

A class of unusual lightning electric field waveforms with very strong high‐frequency radiation

Abstract: The first wideband dE/dt recordings have been obtained for the narrow bipolar pulses previously identified by Le Vine (1980) as “sources of the strongest RF radiation from lightning.” These dE/dt waveforms are dramatically different from those of other known lightning processes. A burst of high‐frequency “noise” is superimposed on the slower bipolar pattern one might expect from the relatively smooth E waveforms. For 18 such pulses from an isolated thunderstorm cell at known range, the mean peak E and dE/dt, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
213
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(238 citation statements)
references
References 18 publications
(16 reference statements)
23
213
1
Order By: Relevance
“…For this limited dataset that has LASA ground-truth on whether the coincidence is from an NBE, it appears that NBE-coincident VHF events show no significant pattern of proximity to flash neighbors, unlike the non-NBE-coincident VHF events. This would tend to agree with the earliest, pre-LMA reports (Le Vine, 1980;Willett et al, 1989).…”
Section: Probability Of Flash Neighbors Of Forte Vhf Tippssupporting
confidence: 77%
See 4 more Smart Citations
“…For this limited dataset that has LASA ground-truth on whether the coincidence is from an NBE, it appears that NBE-coincident VHF events show no significant pattern of proximity to flash neighbors, unlike the non-NBE-coincident VHF events. This would tend to agree with the earliest, pre-LMA reports (Le Vine, 1980;Willett et al, 1989).…”
Section: Probability Of Flash Neighbors Of Forte Vhf Tippssupporting
confidence: 77%
“…8-11 of the present study confirm that at the high VHF TIPP ERP ranges, say >30 kW, the likelihood of prompt concurrence above the PDD threshold (top-of-cloud peak emission power ∼ 3×10 8 W) falls monotonically versus increasing ERP. We remark that since the earliest report of NBE sferics (Le Vine, 1980), all studies of this phenomenon have observed that NBE sferics are synchronously accompanied by the most intense VHF emissions of any lightning Jacobson and Light, 2003;Nag andRakov, 2009, 2010a, b;Nag et al, 2010;Smith, 1998;Thomas et al, 2001;Willett et al, 1989Willett et al, , 1990Willett and Krider, 2000). Thus, the results of Figs.…”
mentioning
confidence: 55%
See 3 more Smart Citations